INTEGRATION OF SUSTAINABLE VALUES EDUCATION IN CHEMISTRY LEARNING THROUGH CASE-BASED LEARNING APPROACH TO IMPROVE SCIENCE LITERACY - Manullang, Enjelika; Daulay, Rabiah Afifah; Nadira, Fathin; Sihaloho, Kayra Aprilia Yosephin; Azhara, Nazwa; Nazihah, Nazwa (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Chemistry education has a strategic role in shaping students'awareness of global sustainability issues such as climate change andpollution. This study aims to analyze the effectiveness of Case-Based Learning (CBL) in integrating sustainability values intochemistry learning, while improving students' scientific literacy andcritical thinking skills. The method used is a literature study byanalyzing various sources, including journals, books, and relatedarticles. The results of the study indicate that the CBL approachsuccessfully connects chemical concepts (eg polymers and greenchemistry) with actual issues such as plastic waste and renewableenergy, so that learning becomes more contextual. In addition, thecombination of CBL with STEM-based Project-Based Learning(PjBL) has been shown to train students in problem analysis, data-based decision-making and sustainable solution development.Implementation challenges include lack of teacher training andlimited resources, which can be overcome through pedagogicaltraining, collaboration with industry, and utilization of technology(such as augmented reality). The conclusion of the study confirmsthat the integration of CBL and sustainability values in thechemistry curriculum not only strengthens scientific understandingbut also shapes students' characters who care about theenvironment. Recommendations for further research include long erm evaluation of the impact of CBL on student behavior as well the development of local wisdom-based modules (ethnoscience)